(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study investigates the intricate interplay between adoption rates of various practices, levels of knowledge, and a spectrum of socio-personal, economic, psychological, and communication characteristics within the context of Panna Block, situated in Panna District. With increasing emphasis on sustainable development and community empowerment, understanding the dynamics of adoption behaviors and their underlying determinants becomes imperative. Through a mixed-method approach comprising surveys, interviews, and observational studies, data was collected from a diverse sample representing the demographic spectrum of the Panna Block population. The study identifies correlations between adoption rates and the socio-economic status of individuals, highlighting the role of education, income, and access to resources in influencing adoption behaviors. Furthermore, the analysis delves into the psychological factors such as attitudes, beliefs, and perceptions that shape individuals’ willingness to adopt new practices. Moreover, the study examines the role of interpersonal communication and community networks in facilitating or hindering the spread of adoption.